Optimizing the Anabolic Response in Sedentary Populations: A Review of Resistance Training Variables and Nutritional Modulators of the IGF-1 Axis - Kaminskaya, Anhelina; Kurek, Aleksandra; Feretycki, Hubert; Salama, Aladdin; Głowacka, Aleksandra; Savchak, Tetiana; Kozicki, Maciej; Górecki, Patryk; Ivanchuk , Sofiia; Domińczak, Dominika; Abdulla, Shafea (Quality in Sport, 2026)
Purpose: This review evaluates how resistance training (RT) variables - intensity, volume, rest intervals, and circadian timing - combined with nutritional factors, influence the IGF-1 axis in sedentary populations. The aim is to establish evidence-based protocols to counteract somatopause, sarcopenia, and metabolic decline, enhancing intervention effectiveness in clinical and fitness settings.Methods: A systematic review was conducted based on 26 research articles, including clinical trials, meta-analyses, and contemporary physiological and nutrigenetic studies. The analysis focused on systemic and local IGF-1 isoforms, such as Mechano-Growth Factor (MGF), and key training parameters: high-load versus low-load methods, set volume, rest duration, and biological rhythms.Results: Resistance training effectively restores the IGF-1 axis in inactive individuals. For beginners, low-load protocols (20–30% 1RM), particularly combined with blood flow restriction or slow-motion techniques, activate the mTOR pathway as effectively as traditional high-load training. These methods significantly mitigate the 20% decrease in arterial compliance often associated with heavy lifting. Furthermore, exercise-induced stress triggers a massive hemodynamic shift, redirecting up to 88% of cardiac output to skeletal muscles to facilitate homeostasis. Optimal adaptation is further supported by longer rest intervals (~3 minutes) and evening workouts. Nutrigenetically, rs6214 "T" allele carriers demonstrate enhanced visceral fat loss when resistance training is paired with daily dairy consumption.Conclusions: Enhancing anabolic responses in sedentary individuals requires a personalized approach. Low-load RT protocols, preferably in the evening, combined with a protein-rich diet tailored to the rs6214 genotype, represent a modern strategy for preventive healthcare. This integrated approach effectively addresses muscle deterioration while ensuring cardiovascular safety and systemic equilibrium.